Propuesta de desarrollo turístico orientada a la promoción de flora y fauna del municipio de Palermo - Huila (2020)
The mayor's office of Palermo aims to develop tourism in the municipality, currently they do not have the ideal infrastructure in places that have potential such as the Colonial Temple, the Bethany chapel, the Santa Rosalía grotto, the Palma Sola hacienda, the Stone Bridge, the Camino Real, the El Juncal lagoon; Tune River sub-basins, waterfalls, the cave and Cerro del Fraile. To do this, a proposal will be diagnosed, analyzed and generated to revitalize the elements that make up the tourism production chain in the municipality in order to promote its economic growth by generating different connection elements between the different places of interest that are located. They find a cultural park in the urban area to attract new tourists. A proposal will be made where tourism, culture and the environment are promoted, added to this a hotel with an eco-friendly orientation where connection with the environment is promoted. All aimed at promoting environmentally friendly tourism and with a strong interest in social inclusion, the central town will connect with the ecotourism offer, strengthening practices such as hiking, climbing, rappelling, kayaking, cycling and encouraging the culture of Pindo, this way to overcome the deficit of tourist attractions in the central town. This will allow the municipality of Palermo to position itself as a tourist provider with national and international recognition.